2006
DOI: 10.1016/j.amjhyper.2006.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Coronary Artery Disease in Patients With Renal Artery Stenosis Without Clinical Manifestations of Coronary Insufficiency

Abstract: Atherosclerotic renal artery stenosis (RAS) and coronary artery disease (CAD) arise from the same multiple risk factors. The purpose of this study was to assess the frequency of previously undiagnosed CAD in patients with angiographically confirmed RAS, by conducting coronary arteriography in the same setting. Of 57 consecutive patients referred for renal arteriography on clinical grounds during a 14-month period, 28 had no RAS and 6 had RAS, but previously documented CAD. Of the remainder 23 patients, 17 (74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…1 Ischemic nephropathy progresses to end-stage renal disease (ESRD) in 6-17% of patients. [2][3][4] RAS is the most common potentially reversible disorder leading to renal replacement therapy. 5,6 Moreover, the presence of RAS has been independently associated with increased mortality, particularly in patients with coronary artery disease (CAD) and ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ischemic nephropathy progresses to end-stage renal disease (ESRD) in 6-17% of patients. [2][3][4] RAS is the most common potentially reversible disorder leading to renal replacement therapy. 5,6 Moreover, the presence of RAS has been independently associated with increased mortality, particularly in patients with coronary artery disease (CAD) and ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence in this important research area is scanty. To the best of our knowledge, there is one single study also from Brazil involving a small number of patients (n = 23) reporting a high prevalence of CAD (74%) in patients with significant RAS [17]. It should be stressed that this preliminary investigation did not systematically evaluate patients at risk of RAS, and the definition of CAD also included patients with less severe coronary stenosis (>50%).…”
Section: Discussionmentioning
confidence: 97%
“…However, this finding was expected considering the high prevalence of RAS in hypertensive patients undergoing angiographic procedures for CAD. De Carvalho found that 74% of patients with RAS had concurrent CAD in one or more coronary arteries, although they had no symptoms of coronary insufficiency [6]. In addition, Ollivier et al reported that among 650 patients suffering from CAD, 94 presented with RAS, corresponding to an estimated prevalence of 14.5%, including 6% of patients with left coronary artery stenosis, 5.4% with right coronary artery stenosis, and 3.1% with bilateral stenosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that coronary artery disease (CAD) is one of the most important causes of death in patients with atherosclerotic RAS. In addition, a high prevalence of RAS has been reported in patients with documented CAD [6][7]. Contrast angiography is a standard method for the detection of RAS that is readily performed in combination with coronary angiography [8].…”
Section: Introductionmentioning
confidence: 99%